Heat therapy for different knee diseases: expert opinion - Rossi, Roberto (Frontiers in Rehabilitation Sciences, 2024)
Musculoskeletal pain is a major burden in our society. Management of musculoskeletal pain or injuries includes both pharmacological and non-pharmacological approaches, including heat therapy (HT). HT is a well-established treatment option due to its ability to promote muscle relaxation, enhance blood circulation, and modulate nociceptors with a good safety profile. The main focus of this paper is to review the available literature about HT in knee pathologies (i.e., arthrosis, arthritis, traumatic pathologies in the subacute phase, muscle and tendon pathologies linked to fatigue, muscle tension and distractions) and to provide an expert opinion in case of lack of data.